(untitled) (Historia, 2021)
L.J. "Wikus" du Plessis (1897-1968), professor of Constitutional Law at Potchefstroom University, wrote to the Executive Council (UR) of the Afrikaner Broederbond on 16 July 1960 announcing his resignation from the organisation. He had been a member of this secret society for almost 37 years and its chairman from 1930 to 1932. His reason for cutting his ties with the very organisation he had helped to make a force to be reckoned with, was a fierce (and in part, public) confrontation with the South African prime minister, Hendrik Verwoerd (1901-1966) about the understanding and implementation of apartheid. Whereas Verwoerd proceeded according to the criteria of political practicability and aimed at the preservation of racial privilege, Du Plessis wanted apartheid to become a social order founded on moral principles. For this reason he demanded that the black population be given realistic economic opportunities. The previous year the same issue had led to Du Plessis’ expulsion from the National Party (NP), a party he had served for more than two decades.